Simulating unsteady transport of nitrogen biochemical oxygen demand, and dissolved oxygen in the Chttahoochee River downstream from Atlanta, Georgia - 262216 Jobson, H. E.; United States. Geological Survey (Alexandra, Va : U S Geological Survey, 1985)
10